2012
DOI: 10.17221/299/2011-pse
|View full text |Cite
|
Sign up to set email alerts
|

The impact of post-anthesis nitrogen and water availability on yield formation of winter wheat

Abstract: The effects of irrigation regimes (full irrigation and water-withholding at anthesis) and post-anthesis nitrogen supplies (LN: 0, MN: 20 and HN: 40 kg N/ha) on grain yield and its components in winter wheat were studied, with attention to biomass gain by assimilation and its loss by respiration. Fully-irrigated wheat responded to N fertilization with increased grain number (GN) and decreased grain weight (GW) and achieved similar grain yields (5.2 to 5.5 t/ha) at different N supplies. However, drought-stressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
2
9
1
4
Order By: Relevance
“…This confirms the results of Jia et al (2012), who found that drought or excess water led to less and smaller GMP formed, indicating irrigation levels influenced both glutenin biosyn- thesis and glutenin particle formation. These data have shown that water availability and genotype are important factors that influence the formation of yield and flour quality, which is consistent with the results of Madani et al (2012). While managing for wheat yield and quality, growers should consider both the water and genotype factors to improve the end-use quality of wheat.…”
Section: Discussionsupporting
confidence: 86%
“…This confirms the results of Jia et al (2012), who found that drought or excess water led to less and smaller GMP formed, indicating irrigation levels influenced both glutenin biosyn- thesis and glutenin particle formation. These data have shown that water availability and genotype are important factors that influence the formation of yield and flour quality, which is consistent with the results of Madani et al (2012). While managing for wheat yield and quality, growers should consider both the water and genotype factors to improve the end-use quality of wheat.…”
Section: Discussionsupporting
confidence: 86%
“…Water deficiency restricts normal crop growth resulting in enormous yield loss. However, the presence of available SWC encourages extensive root development which can occupy a large soil mass and increase water and nutrient absorption, resulting in enhanced growth characteristics and higher tomato yield (Warner et al, 2002;Ismail et al, , 2008Law-Ogbomo and Egharevba, 2009;Madani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient solution was provided once a week using Volldünger Classic water-soluble fertilizer (Kwizda Agro Ltd., Vienna, Austria). The drought stress was generated by total water withholding for 7 days from the 5 th day after heading (Madani et al 2012, Varga et al 2012). Weight of the pots was constant at the end of the stress treatments, as the result of which the volumetric soil water content measured using 5TE soil moisture sensors (Decagon Devices Ltd., Pullman, USA) dropped from the control value of 20-25% to 3-5%.…”
Section: Methodsmentioning
confidence: 99%